INTERNATIONAL LEGAL STANDARDS OF CRIMINAL-LEGAL PROTECTION AGAINST VIOLENCE AT SPORTS EVENTS - Stevanovic, Nemanja; Radulović, Dušan (The Policy of National Security, 2023)
The aim of the paper is to present the effectiveness of the mechanisms used so far to prevent violence and unsuitable behavior at sports events, contained in the international legal framework and national legislation, and which arose from the practice of opposing this form of violence in certain countries of Western Europe. International cooperation in the field of criminal-legal protection against violence at sports events developed after a series of tragic events in the second half of the 20th century, with the intention of establishing a system of preventive action through the power of laws and international conventions in order to eliminate unpleasant scenes from the content of sports activities. As certain societies, especially those in the process of transition, ignore the importance of the health and recreational function of sports, at the same time they do not do enough in terms of this prevention and change of those social relations that are at the foundation of the deviant behavior of sports actors, primarily fans. Based on the qualitative analysis of the literature, as a basic methodological approach and the analysis of the legal and institutional framework in this area, it is declared that many useful and effective steps have been taken in this field in the last few decades.  However, as violence at sports events still exists as an unavoidable  feature of almost every activity of this kind, on the fields and in the halls throughout Europe, we could note that there is some room for further progress in terms of the defined goal. Using cheering as a defense mechanism of identification, where the very competitive relationship within the game creates rivalry, these members of mostly marginalized social groups in this way articulate their dissatisfaction in a socially unacceptable way.
Keywords: sport; fans; law; hooligans; sports violence; international legal framework; extremism